(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article presents a critical analysis and overview of interdisciplinary approaches developed and applied by us to solve key problems in modern space science, including astrobiology, space radiophysics, and medicine. We focus on the prospects for finding extraterrestrial life through detailed study of the Earth’s cryobiosphere and its niches in the context of Mars. In addition, we present the results of radiophysical studies of the solar wind and planetary ionospheres, as well as new methods for global monitoring of the Earth’s ionosphere. In the field of space medicine, we analyze data from the ground-based Mars-500 experiment, aimed at identifying osological conditions under the influence of extreme climatic and environmental factors. In conclusion, we describe the architecture of the research documentation automation system (SADI) required for the management and analysis of complex technical systems in the MARS multilevel modeling environment (SMM MARS).